Impact of human resource management organisations' performance: empirical evidence from small and medium-sized enterprises in the Slovak Republic - Samuel Body; Lukrécia Hunková; Katarína Havierniková (Entrepreneurship and Sustainability Issues)
Effective human resource management is currently acknowledged as a crucial factor in supporting the performance and sustainability of organisations. The evidence base in this area is growing, and there is a growing consensus that effective human resource management is a key driver of organisational success. This gap is particularly evident in the context of SMEs, where effective HRM systems can be vital for long-term success. This study addresses the aforementioned research gap by identifying the relationship between high-performance work systems (HPWS) and innovation performance (IP), as well as between human resource management practices (HRMP) and innovation performance (IP) in small and medium-sized enterprises (SMEs). The data were obtained from small and medium-sized enterprises (SMEs) operating in the Slovak Republic and subsequently analysed using Kendall's Tau-b. The results demonstrated a statistically significant moderate positive correlation between the examined variables, indicating that high-performance work systems (HPWS) and human resource management practices (HRMP) have a positive impact on the innovation performance of SMEs. In light of the findings presented here, we propose that further research be conducted to examine the long-term effects and optimisation of coherent HRM systems across various organisational types. Further research should investigate how these systems can foster employee engagement, reinforce an innovation culture, and enhance the company's overall performance over an extended period.